Effect of Acute Moderate-Intensity Exercise on the Mirror Neuron System: Role of Cardiovascular Fitness Level - Xu, Zebo; Wang, Zi-Rong; Li, Jin; Hu, Min; Xiang, Ming-Qiang (Frontiers in Psychology, 2020)
ABSTRACT Objectives: The aims of this study were to use Functional Near-Infrared Spectroscopy (fNIRS) to determine whether cardiovascular ﬁtness levels modulate the activation of the mirror neuron system under table-setting tasks in non-exercise situation, to replicate the study that positive effect of acute moderate-intensity exercise on the mirror neuron system (MNS) and investigate whether cardiovascular ﬁtness levels modulates the effect of exercise on the activation of the MNS. Methods: Thirty-six healthy college-aged participants completed a maximal graded exercise test and were categorized as high, moderate, or low cardiovascular ﬁtness. Participants then performed table-setting tasks including an action execution task (EXEC) and action observation task (OBS) prior to (PRE) and after (POST) either a rest condition (CTRL) or a cycling exercise condition (EXP). The EXP condition consisted of a 5-min warm-up, 15-min moderate-intensity exercise (65% VO2max), and 5-min cool-down. Results: No significant differences were observed for Oxy-Hb and Deoxy-Hb between different cardiovascular fitness levels in the EXEC or OBS tasks in the non-exercise session. But there were significant improvements of oxygenated hemoglobin (Oxy-Hb) in the IFG and PMC regions under the OBS task following the acute moderate exercise. Particularly, the improvements (Post-Pre) of Δ Oxy-Hb were mainly observed in high- and low- fitness individuals. There was also a significant improvement of deoxygenated hemoglobin (Deoxy-Hb) in the IPL region under the OBS task. The following analysis indicated that exercise improved Δ Deoxy-Hb in high fitness individuals. Conclusion: This study indicated the activation of MNS was not modulated by the cardiovascular fitness levels in the non-exercise situation. We replicated the previous study that moderate exercise improved activation of MNS; we also provided the first empirical evidence that moderate-intensity exercise positively affects the MNS activation in college students of high and low cardiovascular fitness levels.